Manufacture of aviation parts from heat-related nickel alloys by multilayer plasma surfacing - Михайло Олегович Гнатенко (National Aerospace University «Kharkiv Aviation Institute», 2021)
The aviation part of the ring-type was made of heat-resistant structural alloy EI 868 (HN60VT) by the method of additive multilayer plasma surfacing with wire. The traditional technology for obtaining this type of ring blank is the stamping of rods, which are then brought to the final shape of the part by further machining. The disadvantage of traditional technology is the significant cost of metal, which in the process of machining the pressed rod, is converted into chips and not reused, which increases the cost of the finished product. The use of additive technologies will significantly reduce the cost of material in obtaining annular workpieces by manufacturing a workpiece with a configuration as close as possible to the geometry of the part. Additive surfacing was performed on a robotic complex consisting of a plasma power supply SBI PMI-350 AC/DC TL and work FANUC M-710iC on a rigidly fixed substrate of steel 20. To determine the possibility of obtaining aviation parts using the method of layer-by-layer plasma surfacing, a study of the deposited material was conducted The structure of the grown part was studied, it was found that the microstructure corresponds to the normal state of the alloy EI868 (HN60W) in the microstructure of the fusion line is not visible, the structure is homogeneous with the mutual germination of grains between layers. Alloy parts obtained using the method of additive cultivation are at the level of cast blanks and forgings and at T = 900oC are: sв =35±5 кгс/мм2,s0,2 =49±5 кгс/мм2, y = 62±5 %. After machining the grown workpiece, a capillary method of control and radiation control of the grown part - cracks and other types of critical metallurgical defects was not detected. The practical significance of the introduction of this method is a significant reduction in material costs in obtaining parts and ensuring economic efficiency, which is about 159 thousand hryvnias.